Crystal Structure, Solubility, and Pharmacokinetic Study on a Hesperetin Cocrystal with Piperine as Coformer - Yanjie Liu; Fan Yang; Xiuhua Zhao; Siying Wang; Qilei Yang; Xiaoxue Zhang (MDPI AG, 2022)
Hesperetin (HES) is a key biological active ingredient in citrus peels, and is one of the natural flavonoids that attract the attention of researchers due to its numerous therapeutic bioactivities that have been identified in vitro. As a bioenhancer, piperine (PIP) can effectively improve the absorption of insoluble drugs in vivo. In the present study, a cocrystal of HES and PIP was successfully obtained through solution crystallization. The single-crystal structure was illustrated and comprehensive characterization of the cocrystal was conducted. The cocrystal was formed by two drug molecules at a molar ratio of 1:1, which contained O-H-O hydrogen bonds between the carbonyl and ether oxygen of PIP and the phenolic hydroxyl group of HES. In addition, a solubility experiment was performed on powder cocrystal in simulated gastrointestinal fluid, and the result revealed that the cocrystal improves the dissolution behavior of HES compared with that of the pure substance. Furthermore, HES's bioavailability in the cocrystal was six times higher than that of pristine drugs. These results may provide an efficient oral formulation for HES.